1965
DOI: 10.1002/art.1780080611
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of monosodium urate needle crystal growth

Abstract: A study of the growth of needle crystals of monosodium urate was undertaken with the aim of finding inhibitors which might be able to prevent the acute gout attack. Rates of crystal growth at various levels of supersaturation are described. Two potent crystal growth inhibitors, Bismarck brown and methylene blue, were found. They are shown to be adsorbed onto monosodium urate. THAM was found to accelerate needle crystal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 5 publications
(1 reference statement)
2
27
0
Order By: Relevance
“…An approximate heat of dissolution of 4.9(3) kcal/mol (in TMT) could be computed from these data. A similar value (5.5 kcal/mol) can be calculated from data given by Allen et al 8 for the solution of monosodium urate in water. These values may be compared with the heats of dissolution for uric acid dihydrate where a much larger difference (4.0 kcal/mol in TRIS buffer and 15.4 kcal/mol in water) was found and attributed to the exothermic acid-base reaction H 2 U+TRIS"HU -+TRISH + that occurs in the dissolution of uric acid.…”
Section: Dissolving Ability Valuessupporting
confidence: 78%
See 1 more Smart Citation
“…An approximate heat of dissolution of 4.9(3) kcal/mol (in TMT) could be computed from these data. A similar value (5.5 kcal/mol) can be calculated from data given by Allen et al 8 for the solution of monosodium urate in water. These values may be compared with the heats of dissolution for uric acid dihydrate where a much larger difference (4.0 kcal/mol in TRIS buffer and 15.4 kcal/mol in water) was found and attributed to the exothermic acid-base reaction H 2 U+TRIS"HU -+TRISH + that occurs in the dissolution of uric acid.…”
Section: Dissolving Ability Valuessupporting
confidence: 78%
“…Another peculiarity of MSU is that its formation is clearly related to high levels of urate in the blood serum (uricemia) but, although necessary, this condition is not sufficient to provoke gout, either because crystallization in the synovial liquid may be inhibited or because the crystals are somehow blocked to develop their pathogenic actions. 6,7 Much ongoing research is concerned with these facts and it seems that surface covering of crystal faces may play a role, [8][9][10][11] but the therapy of gout is so far restricted to the symptomatic treatment of the inflammation itself and to the prevention of urate crystal formation through the control of uricemia, either reducing the urate production from purine (e.g. using xanthine oxidase inhibitors) or increasing the rate of uric acid elimination (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The latter two urate preparations were used in all experiments except those in which the effects ofsodium concentration and of ultrafiltration of plasma were studied. It is clear that temperature plays a significant role in urate solubility and this has been discussed previously (Wilcox and others, 1972;Allen, Milosovich, and Mattocks, 1965). Loeb (1972) suggested that the predilection of gout for the peripheral parts of the body is due to sustained lower temperatures in these areas.…”
Section: Urate Solubility In Biological Fluidsmentioning
confidence: 73%
“…Uric acid is a weak organic acid (pKa, 5.75); at pH 7.40 and at 37º C, about 98% of uric acid is ionized as monosodium urate. Solubility studies have determined that at the sodium concentrations prevailing in extracellular fluids, serum is supersaturated for monosodium urate at concentrations above 6.5 mg/dL [5]. This provides a physical chemical definition of hyperuricemia.…”
Section: Definition and Causes Of Hyperuricemiamentioning
confidence: 99%